Modern possibilities for expanding complex therapy of postpartum septic complications. (Eurasian Medical Research Periodical, 2024)
In modern obstetrics, the medical and social significance of infections is due to their significant contribution to the formation of maternal morbidity and mortality rates [1–3]. Despite significant advances in diagnosis and antimicrobial therapy, according to the conclusions of WHO experts [4], the share of postpartum sepsis in the structure of maternal mortality in the world is quite high.